Initiatives and exposures associated with food security in remote and isolated communities: a scoping review - Mallory Drysdale; Kelly Skinner; Calin Lazarescu; Alix Couture; Shelley Young; Leanne Idzerda (James Cook University, 2024)
Introduction: Chronic household food insecurity (HFI) and lack of food availability and accessibility in isolated communities are longstanding public health crises. This review aims to paint a more fulsome picture of food security initiatives in remote and isolated communities by examining programs across circumpolar countries, Australia, and Aotearoa New Zealand. This synthesis of research will contribute to an understanding of what types of initiatives exist and aid in the identification of best practices. Methods: The authors conducted a scoping review identifying articles that include either (1) an evaluation of an initiative with a quantitative food security outcome in remote and isolated communities, or (2) quantitative associations between exposure factors with food security outcomes. Inclusion criteria included English and French articles focused on remote and isolated communities in Canada, the US, Australia, New Zealand, Sweden, Norway, Finland, Greenland, and Russia from January 1997 to July 2022. Results: The article search yielded 1882 results, of which 96 fulfilled the inclusion criteria, including 26 studies evaluating initiatives, 66 studies evaluating exposure factors, and four studies that included both initiatives and exposure factors. The majority of the studies included in this review were conducted in Canada and Australia. No initiative studies conducted in Russia, Greenland, Norway, Finland, or Sweden fulfilled the criteria for inclusion in this review. The most common types of initiatives evaluated included school-based programs, market subsidies, and education initiatives, though a small number (<5) of other programs were evaluated, including traditional food programs and greenhouses. Though multiple programs resulted in lower food costs or increases in healthy food consumption in remote regions, the cost of a healthy diet in these areas remained high, as do levels of HFI. Factors associated with improved food security outcomes included higher income level, access to adequate housing, higher education level, access to transportation for harvesting, and the level of remoteness of a community. The studies included in this review also stressed the importance of access to and affordability of harvesting traditional foods in these regions. Conclusion: Those living in remote and isolated communities are particularly vulnerable to food insecurity and lack of access and availability of healthy foods, which are compounded by a variety of socioeconomic factors. This study highlights the lack of quantitative evaluations of food security initiatives in remote and isolated communities, as well as the wide variety in measured outcomes. Authors of several of the included articles note that community-led initiatives, with strong partnerships and local champions, were recommended in these populations, given the culturally and geographically diverse groups living in remote and isolated areas.